HUKUM PERKAWINAN DI INDONESIA (MARRIAGE LAW IN INDONESIA) - Penasthika, Priskila Pratita (UI Scholars Hub, 2012)
Human is social being who during his or her life will always be in interaction with the other human. Marriage is one form of interactions that could happen between human being. Every state in this world has its own regulation to determine the requirements and procedure for a legal marriage . As reflected in its title, this book, specifically discusses specifically the marriage law in Indonesia.